Malaria : Perceptions and treatment practices among mothers of children under 10 years in rural Ghana - Eckhardt, Stefan; Justus Liebig University Giessen (My University, 2004)
Background: Malaria is one of the diseases which contributes significantly to morbidity and mortality in Africa. 90% of the estimated 300-500 Million malaria cases per year worldwide occur in sub-Sahara Africa. There are at least one million deaths attributed to malaria every year in Africa. To reduce childhood mortality, early and adequate treatment of malaria is essential. In areas of intense transmission, WHO, therefore, recommends all children with fever to be presumptively treated with antimalarials, as part of the strategy of Integrated Management of Childhood Illnesses(IMCI). The need for early adequate treatment, the poor accessibility of health posts and the economic situation, especially in Sub-Saharan Africa, make self-medication and treatment at home often the only option for receiving any kind of treatment. This paper describes health seeking behaviors, as well as perceptions of malaria used as diagnostic criteria and judgment on severity of malaria. The quality of drug treatment is investigated in detail (self medication and outpatient treatment at official health providers) and compared to the treatment standards. Factors contributing to the actual treatment seeking behavior, in particular inner-household decision making dynamics among mothers and fathers, are analyzed. Methods: The study was carried out in the Juansa and Agogo sub-districts of Asante Akim North District in the Asante Region of Ghana. The Asante Akim North district is a holoendemic malaria area. In the Asante Region an overall prevalence of parasitaemia of 49.7-50.7 % was found in the period February April 1998 with Plasmodium falciparum as the predominant species.The study was designed as a cross sectional survey. This study combined both qualitative and quantitative data collection methods to provide a broad understanding of factors and the context influencing mothers´ and fathers´ definition and treatment of childhood malaria. Besides Focus Group Discussions, 1;885 caretakers of children <10 years old and 955 of their husbands were interviewed using a structured questionnaire. Treatment strategies were investigated for perceived malaria episodes within the last 4 weeks preceding the interviews. Results: Fever was perceived as the leading symptom of malaria by 76.4% of mothers and 78.8% of fathers. All study methods applied indicated that fever was solely measured by touch. Out of 801 perceived malaria episodes reported, self-treatment was done within 48 hours after onset of symptoms in 662 (82.6%), non-layperson treatment in 168 (21%). As self-medication, only 329 children (49.7%) received antimalarials, the majority of them Chloroquine. Out of 250 children who received self-administered antimalarials and for whom information on dosage was available, only 14 (5.6%) received a correct dosage. Over-dosages occurred frequently. 576 (71.9%) of the caretakers were married; information on decision dynamics was available from 573 of them. In about two thirds of these cases, the final treatment decision was made by the husband, who was also responsible for the payment in 77.5% of the cases. Conclusions: Self-treatment at home is the most prevalent action taken to manage malaria. The quality of home treatment is low. Efforts should be made to improve home treatment and drug compliance through the availability of pre-packed drugs and the introduction of community health workers. In the face of frequently encountered over-dosages, particularly in infants and the low specificity of the symptom fever, the diagnosis of fever should be more accurate. The use of fever thermometers by community health workers should therefore be considered in order to avoid unnecessary exposure to adverse drug effects due to misdiagnosis of fever, particularly in infants. Furthermore the role of the husband has to be given more adequate consideration in the planning of malaria control programs. Although further investigations into the decision dynamics at household level are clearly needed, it seems to be evident that interventions to improve early treatment of childhood malaria should include both parents.

Hintergrund: Malaria ist in signifikantem Ausmaß für Morbidität und Mortalität in Afrika verantwortlich. Von geschätzten jährlich 300-500 Millionen Malariafällen weltweit treten 90% im Afrika südlich der Sahara auf. Mindestens 1 Million Todesfälle sind jedes Jahr der Malaria zuzuschreiben. Um die Kindersterblichkeit zu senken, ist eine frühzeitige und adäquate Behandlung der Malaria unerläßlich. In Gebieten mit sehr hoher Transmissionsrate rät die WHO daher, als Teil der Integrated Management of Childhood Illnesses (IMCI)- Strategie, alle Kinder mit Fieber als Malariaverdachtsfall mit Antimalariamitteln zu behandeln. Die Notwendigkeit einer frühen adäquaten Behandlung, die schlechte Erreichbarkeit von Gesundheitsposten und die schlechte wirtschaftliche Situation vor allem im Afrika südlich der Sahara, machen Selbstmedikation und behandlung der Malaria oft zur einzigen Option. Die vorliegende Arbeit beschreibt Art des Gesundheitsverhaltens und vorhandenes Wissen über Malaria, das als diagnostische Grundlage zur Einschätzung der Schwere der Malariaerkrankung dient. Die Qualität der Pharmakotherapie der Malaria wird im Detail untersucht (Selbstmedikation und ambulante Behandlung bei offiziellen Gesundheitsversorgern) und mit den offiziellen Behandlungsstandards verglichen. Desweiteren werden Faktoren analysiert, die zum Gesundheits- und Behandlungsverhalten beitragen, insbesondere haushaltsinterne Entscheidungsdynamiken bei Müttern und Vätern. Methoden: Die Studie wurde in den Bezirken Juansa und Agogo des Asante Akim North Districts der Ashanti-Region in Ghana durchgeführt. Im Asante Akim North District tritt Malaria holoendemisch auf. In der Zeit von Februar bis April 1998 wurde in der Asante-Region eine Parasitämieprävalenz von 49.7-50.7 % ermittelt. Die prädominante Parasitenspezies war dabei Plasmodium falciparum. Die Studie wurde als Querschnittsstudie konzipiert. Um ein umfassendes Verständnis der Faktoren zu erhalten, die seitens der Eltern die Erkennung und Behandlung der Malaria ihrer Kinder beeinflussen, kamen dabei sowohl qualitative wie quantitative Datenerhebungsmethoden zum Einsatz. Neben Fokus-Gruppendiskussionen wurden 1885 Mütter von Kindern unter 10 Jahren sowie 955 Ehemänner mit Hilfe eines strukturierten Fragebogens befragt. Es wurden die Behandlungsstrategien von erkannten Malariaepisoden bis 4 Wochen vor dem Interview untersucht. Ergebnisse: Fieber wurde von 76.4% der Mütter und 78.8% der Väter als Leitsymptom der Malaria angesehen. Alle angewandten Studienmethoden zeigten, daß Fieber nur durch Auflegen der Hand 'gemessen' wurde. Von berichteten 801 erkannten Malariaepisoden wurde eine Selbstbehandlung innerhalb 48 Stunden in 662 (82.6%) Fällen und eine professionellen Behandlung in 168 (21%) Fällen durchgeführt. Als Selbstmedikation erhielten nur 329 Kinder (49.7%) Antimalaria-Medikamente, mehrheitlich davon Chloroquin. Von 250 Kindern, die selbstverabreichte Antimalaria-Medikamente erhielten und bei denen Dosierungsinformationen ermittelt werden konnten, erhielten nur 14 (5.6%) die richtige Dosierung. Überdosierungen kamen häufig vor. 576 Mütter (71.9%) waren verheiratet und Informationen über Entscheidungsdynamiken waren bei 573 erhältlich. In ungefähr 2/3 der Fälle wurde die endgültige Behandlungsentscheidung vom Ehemann getroffen, der dann auch in 77.5% der Fälle für die Bezahlung der Behandlung verantwortlich war. Schlußfolgerung: Häusliche Selbstbehandlung ist die häufigste Maßnahme, die zur Malariatherapie ergriffen wird. Die Qualität der häuslichen Selbstbehandlung ist niedrig. Es sollten Anstrengungen unternommen werden, die die häusliche Selbstbehandlung und die Medikamentencompliance verbessern, wie etwa vorgepackte Medikamente und die Einführung von Community-Gesundheitsarbeitern. Angesichts der insbesondere bei Säuglingen häufig vorkommenden Überdosierungen und der niedrigen Spezifität des Symptoms Fieber, sollte die Diagnose Fieber akkurater gestellt werden. Es sollte daher der Einsatz von Fieberthermometern durch die Community-Gesundheitsarbeiter erwogen werden, um nicht die Kinder und vor allem Säuglinge durch die Fehldiagnose Fieber unnötig dem Risiko schwerer Medikamentennebenwirkungen auszusetzen. Desweiteren muß bei der Planung von Malaria-Kontrollprogrammen die Rolle des Ehemannes adäquater beachtet und untersucht werden. Obgleich weitere Untersuchungen der Entschlußdynamiken in den Haushalten auf jeden Fall erforderlich sind, scheint es evident zu sein, daß bei Maßnahmen zur Verbesserung der Frühbehandlung der kindlichen Malaria beide Elternteile einbezogen werden müssen.
Malaria : Praxis der Erkennung und Behandlung bei Müttern von Kindern unter 10 Jahren in ländlichenTeilen Ghanas
Keywords: Malaria; Selbstmedikation; Ghana; Mikrozensus; Malariaerkennung; malaria; self treatment; perceptions; micro census; Ghana; ddc:610